Juridical Review of Advocates In Providing Free Legal Aid to Perpetrators of Narcotics Abuse Crimes - Leonardo Sibarani, Baginda Victor; Sihotang, Erikson; Suandika, I Nyoman (International Journal Labs, 2024)
The authority of advocates in providing legal assistance to perpetrators of narcotics abuse crimes, as stipulated in Article 55 paragraph (1) of the Advocate Law, gives status to advocates as law enforcers who have an equal position with other law enforcers in upholding law and justice. Legal aid provided by advocates for free is a right owned by a person who has the status of a defendant to the perpetrator of narcotics crimes. The obstacles and solutions faced by advocates in providing legal aid to perpetrators of narcotics abuse crimes, namely the lack of legal knowledge and awareness in the community itself about the Legal Aid Process that they only know from the information of the public in general is one of the obstacles in the process of providing Legal Aid